FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI (SIA) BANK PEMERINTAH (Studi Empiris Pada Bank Umum Pemerintah Di Kota Surabaya) - Fatmawati Fatmawati; Moh. Amin Moh. Amin; Afifudin Afifudin (Universitas Islam Malang, 2017)
The purpose of this study is to determine the factors that affect the performance of accounting information system of public banks in the city of Surabaya. This study uses multiple linear regression analysis with the SPSS software (statistica and service solution) for windows. The method used for data collection tool is using questionnaire method. The data obtained is by distributing questionnaires to the users of SIA on bank BTN and bank JATIM. From the results of questionnaires sent to the respondents as many as 32 questionnaires that can be processed in this study. The results of this study show that the results of t test (partial) with a significance level smaller than 0.05 indicates there are 5 independent variables (X) that does not affect the dependent variable (Y), that is; Ability of personal technique system (X2), formalization of information system development (X5), user education and training programs (X6), information systems management boards (X7), and Locations of information systems departments (X8). While the size of the organization (X3), and top management support (X4) have a positive effect on the dependent variable (Y). However, user involvement in the development of SIA (X1) negatively affects the dependent variable (Y).